Reducing Tantrum Behavior In Autistic Children Through “Isolationary Time-Out” Type Of Time Out Techniques - Mirnawati Mirnawati; Amka Amka (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the effectiveness of the "isolationary time out" type of time out technique in reducing tantrum behavior in autistic children, in this study the tantrum behavior in question is hitting behavior. The research approach used is quantitative with the type of experimental research with a Single Subject Research (SSR) approach. The design used is A1–B–A2. The research subject is an autistic student at SDLB YPLB Banjarmasin. The data recording technique uses event recording by measuring the frequency or number of occurrences of tantrum behavior in autistic children. The data obtained were analyzed through descriptive statistics and displayed in graphical form. The components analyzed are analysis under conditions and analysis between conditions. Based on the results of the study, there was a decrease in the frequency of tantrum behavior in autistic children in the baseline-1 (A1) condition, the mean level of tantrum behavior frequency was 14 times. At the time of intervention (B) the mean level of tantrum behavior was 11 times. In the baseline-2 condition (A2), the mean frequency level of tantrum behavior (hitting) was 9 times. Thus it can be concluded that the use of the isolationary time out type of technique is effective in reducing tantrum behavior in autistic children.